Microfluidics for the spectroscopy of carbon nanotubes - Pekkala, Ilkka (2013)
We have successfully finalized the process of creating small microfluidic channels on glass chips, having 4 inlet/outlet holes for liquid flow. The fabricated channel structures can be as complex as electron beam lithography can make them. Working channels have the minimum width and depth of 4 µm x 4 µm.